Patterns of locomotor regulation during the pole vault approach phase - Needham, L.; Exell, T. A.; Bezodis, I. N.; Irwin, G. (Journal of Sports Sciences, 2018)
A successful approach phase is key to achieving high performances in the pole vault. The aim of this study was to explore the nature of locomotor control patterns during the pole vault approach phase. Fourteen well-trained athletes performed ten jumps which were recorded using 2D video sampling at 200 Hz and analysed. Key kinematics were reconstructed from camera data using a modified 2D-DLT. Patterns of regulation were determined from the standard deviation of footfall locations during the approach phase. These patterns were found to be highly individual but structural differences between those who did and those who did not regulate were identified. Regulation of locomotion was associated with an ability to produce functionally adaptable movement patterns and the consistent achievement of desired performance outcomes. Coaches should include training exercises that require intentional use of regulation to aid athletes in achieving the flexibility to adapt to changing constraints during the approach phase. Athletes should be considered on an individual basis in order to effectively, efficiently and safely improve performance.